1999
DOI: 10.1038/sj.bjp.0702926
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the acute and chronic effects of reboxetine on extracellular noradrenaline and other monoamines in the rat brain

Abstract: 1 The e ect of reboxetine, a novel antidepressant drug that potently and selectively inhibits neuronal noradrenaline (NA) uptake, on brain extracellular monoamines was studied by microdialysis. 2 Fifteen mg kg 71 i.p. reboxetine raised extracellular NA in the frontal cortex (by 242%) and dorsal hippocampus (by 240%). 3 Idazoxan (1 mg kg 71 s.c.), given 60 min after 15 mg kg 71 reboxetine, markedly potentiated the e ect on extracellular NA in the frontal cortex (by 1580%) and dorsal hippocampus (by 1360%), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 22 publications
7
65
0
Order By: Relevance
“…Reboxetine increased NE EX (Sacchetti et al 1999) and DA EX in the PFC to similar levels and to about the same magnitude as found with atomoxetine, consistent with previous reports (Linnèr et al 2001). In the PFC, methylphenidate caused large increases in NE EX and DA EX , but the increases were of short duration in agreement with previous studies (During et al 1992), and consistent with a short duration of action in humans.…”
Section: Discussionsupporting
confidence: 92%
“…Reboxetine increased NE EX (Sacchetti et al 1999) and DA EX in the PFC to similar levels and to about the same magnitude as found with atomoxetine, consistent with previous reports (Linnèr et al 2001). In the PFC, methylphenidate caused large increases in NE EX and DA EX , but the increases were of short duration in agreement with previous studies (During et al 1992), and consistent with a short duration of action in humans.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are also consistent with the results of microdialysis studies showing that acute reboxetine administration (15 mg/ kg, i.p.) produces an increased level of NE in the dialysates in the frontal cortex and dorsal hippocampus without altering that of 5-HT in the striatum (Sacchetti et al 1999). When considered together with biochemical binding data on the transporter (Wong et al 2000), such results confirm that acutely administered reboxetine selectively blocks the NE reuptake transporter in vivo without altering the function of the 5-HT reuptake transporter.…”
Section: Discussionmentioning
confidence: 82%
“…In conclusion, it has been shown that NE availability in the hippocampus is enhanced by reboxetine treatment via blockade of the NE transporter (Sacchetti et al 1999). Since both the acute and long-term administration of reboxetine produced the same degree of enhancement of NE in the extracellular milieu in the same experiments in the hippocampus, the relationship between the delayed clinical response to reboxetine with respect to hippocampal function is not clear.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations